Logical Expressivism and Carroll's Regress. (October 2019) - Besson, Corine
Abstract: In this paper, I address a key argument in favour of logical expressivism, the view that knowing a logical principle such as Modus Ponens is not a cognitive state but a pro-attitude towards drawing certain types of conclusions from certain types of premises. The argument is that logical expressivism is the only view that can take us out of Lewis Carroll's Regress – which suggests that elementary deductive reasoning is impossible. I show that the argument does not hold scrutiny and that logical cognitivism can be vindicated. In the course of the discussion, I draw substantially on a comparison with a similar argument in meta-ethics, for moral expressivism.